Prevalence of Anxiety in Physical Illness Patients - Laili Nur Hidayati; Ari Budi Sri Hidayati (Indonesian Journal of Global Health Research, 2026)
Anxiety patients with physical disorder was characterized by discomfort, sad, restlessness and worried. Patients have physiological, cognitive, affective, behavioral, and social reactions because of their anxiety and fear regarding their condition and the treatment they are receiving. This study aims to analyze the prevalence of anxiety among patients in general hospital. This study uses a cross sectional study carried out amongst 100 patient in general hospital using purposive sampling techniques. A semi-structured questionnaire for the study was used to collect data of the patients used Hospital Anxiety and Depression Scale (HADS) to rate the anxiety symptoms of the patients. HADS has been translated Indonesian languange with good reliability by means inter-rater valuation and analyzed by using Kappa Cohen coefficient (0,706).  Data analysis was done quantitatively using frequency distribution. The study sample consisted of 100 patients with mean age 50,8 years, majority male patients (51%). Based on the HADS scores, 8 patients classified as patients suffering from excessive levels of anxiety, 21 patients had moderate anxiety and 40 patients had mild anxiety. This study found a prevalence of 75% of the patients in general hospital was experiencing anxiety.